2-[(E)-(Naphthalen-2-yl)iminomethyl]phenol - Sharif, Hafiz Muhammad Adeel (International Union of Crystallography, 2012)
In the title compound, C(17)H(13)NO, the azomethine double bond adopts an E conformation. The naphthyl ring system and the benzene ring form a dihedral angle of 8.09 (10)°. The near-planar conformation of the molecule is consolidated by an intramolecular O—H⋯N hydrogen bond, which forms an S(6) ring. In the crystal, molecules are arranged in a zigzag fashion parallel to the c axis.